State and Perspective of Development of Semi-Subsistence Farms in Bulgaria - Mishev, Plamen; Ivanova, Nedka; Shterev, Nikolay; Harizanova, Hristina (Research Papers, 2009)
Agricultural sector in Bulgaria is a traditional one for the national economy. After 2007 it runs in a definitely new economic and political environment. As a member of EU the Bulgarian agricultural producers are obligated to adopt the Common Agricultural Policy (CAP).The agricultural sector has a dualistic structure - in one hand there are large number of small farms, part of them subsistence or semi-subsistence and in the other hand there are only a few number of market oriented units. If the big producers are easier to adherence the legislations of the agricultural sector then it will be very difficult for the small scale farms. Indisputably interest represents the semi- subsistence farms which have a potential to develop to market oriented ones. According to this the Rural development program includes a special measure for semi-subsistence farms to support their development.The main aim in the paper is to reveal the opportunities for development of semi-subsistence farms as a market oriented ones. Based on analysis of their characteristics the conclusions are that positive effects of their development are influenced by better economic environment and improved infrastructure and information services. According to these conditions one third of them have a potential to grow to the market oriented structures.